Arabic sentence between the ancients and modernists. A thorough study - ليث حازم محمود البياتي الموصلي; ابراهيم عبود ياسين السامرائي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The purpose of this research is to study the meanings of the sentence in the Arabic language and to explain the differences between linguists and grammar in ancient and modern terms in the definition of this term by a full survey of the most famous Arabic linguists in this field, and then to study other terms that are somewhat related to this term, And the statement of the views of the grammarians and linguists in them, and then come out with a precise definition of these terms, which is the main reason for this study; because these terms are very ambiguous in their definitions, as there is hardly a single definition of these words, Some are intertwined Biting, as if the word is known as saying, and defines the sentence as a speech, so this study came to address this disorder in the statement of the meanings of these vocabulary. I ask God Almighty to be successful in writing this research and God is the guardian of success.